Methods of the operative forecasting of the change the technical condition of the nodes of the running part gas-turbine engine - Чоха, Ю.М. (Proceedings of National Aviation University, 2005)
Is motivated methods of the realization of the short forecast speakers degrade of the technical condition of the nodes gas-turbine engine on linear model trend diagnostic factor of the node by method least square.